Magnetic resonance imaging in paediatric spinal trauma – retrospective analysis of feasibility, safety, and diagnostic value in the emergency department - Sirén, Aapo (fi=Turun yliopisto|en=University of Turku|, 2024)
Paediatric spinal trauma is a relatively uncommon but challenging entity in the emergency department. Despite the algorithms aiming to exclude spinal trauma based on symptoms and physical examination, medical imaging is often needed. Since the early 20th century, conventional radiography has been the most utilised imaging modality. In recent decades, computed tomography (CT) has become a common primary method, accompanied by magnetic resonance imaging (MRI) as an additional imaging in difficult cases and spinal cord injuries. MRI is more sensitive than CT, but it is unclear if MRI yields additional clinical value compared to CT. MRI is also more expensive, time-consuming, and less available than CT. Long scanning time makes sedation or anaesthesia often mandatory with younger children. The goals of this thesis were to assess the feasibility, safety, and accuracy in emergent spinal trauma imaging of children and adolescents. We retrospectively reviewed the imaging data and medical records of the under-18-year-old patients having undergone spinal MRI at the Emergency Radiology Department of Turku University Hospital 2013–2021 because of acute trauma. MRI demonstrated all injuries requiring surgical treatment. No MRI-related adverse events were reported, and the need for anaesthesia was mainly limited to children aged five years or younger. Unless MRI demonstrated potentially unstable features in spinal injury, the clinical value of follow-up or flexion-extension imaging was low. If the concurrent brain and spine MRI was performed because of a spinal trauma but without symptoms suggesting brain injury, the brain MRI did not reveal any traumatic findings regardless of spinal MRI findings. Our results show that emergency MRI is an accurate, feasible, and safe imaging modality in paediatric spinal trauma. Spinal injury does not seem to be a risk factor for brain injury if no brain injury-related symptoms are present. Emergency MRI reduces the need for follow-up imaging, but assessing MRI's cost-effectiveness or potential superiority over CT as primary imaging requires further studies.

Lasten rankavammojen päivystyksellinen kuvantaminen – takautuva tutkimus magneettikuvauksen käyttökelpoisuudesta, turvallisuudesta ja diagnostisesta merkityksestä Rankavammat ovat moniin lasten ja nuorten vammatyyppeihin verrattuna harvi-naisia. Epäilyn herättyä rankavamman luotettava poissulkeminen oireiden ja klii-nisten tutkimuslöydösten perusteella on hankalaa, joten rankavammaepäily johtaa usein kuvantamistutkimuksiin. Röntgenkuvausta on käytetty rangan tutkimisessa yli sadan vuoden ajan, mutta viimeisten parinkymmenen vuoden aikana tietokone-tomografia (TT) on yleistynyt huomattavasti. Magneettikuvausta (MK) on käytetty täydentävänä tutkimuksena ja erityisesti selkäydinvammaepäilyn yhteydessä. MK osoittaa rangan vammamuutokset herkemmin kuin TT, mutta suuremman herkkyyden merkitys ja hyöty potilaiden hoidossa on toistaiseksi epäselvä. MK on kalliimpi ja hitaampi kuin TT, ja sen saatavuus erityisesti päivystysaikaan on huonompi. Tämän väitöstutkimuksen tarkoituksena oli arvioida MK:n tarkkuutta, turvallisuutta ja toteutettavuutta lasten ja nuorten rankavammaepäilyn vuoksi tehtävänä päivystystutkimuksena. Tutkimuksessa käytiin takautuvasti läpi Turun yliopistollisen keskussairaalan päivystysradiologian yksikössä vuosina 2013–2021 rankavammaepäilyn vuoksi alle 18-vuotiaille potilaille tehtyjen magneettikuvantamisten tiedot sekä muut vammaan liittyvät potilasasiakirjamerkinnät. MK osoitti kaikki kirurgista hoitoa vaativat rankavammat, eikä kuvantamiseen liittyviä haittatapahtumia ilmennyt. Lähes kaikki yli viisivuotiaat pystyttiin kuvantamaan ilman nukutusta. Jos vammassa ei MK:n perusteella ollut huolestuttavia piirteitä, ei seurantakuvauksista ollut lisähyötyä. Lapsilla, joille tehtiin vamman vuoksi samanaikaisesti rangan ja aivojen MK mutta joilla ei ollut aivovammaan viittaavia oireita, ei magneettikuvaus paljastanut aivo-vammaa, vaikka rangassa olisikin todettu vamma. Tulostemme perusteella MK on tarkka ja turvallinen lasten rankavammaepäilyn kuvantamistutkimus. Päivystyksellinen MK vähentää seurantakuvausten tarvetta. Kustannusvaikuttavuuden arviointi kuitenkin vaatii lisätutkimusta, samoin sen selvittäminen, onko MK merkitsevästi parempi kuin TT.